Criteria Assessment in Design Evaluation for Product Development using Integrated Fuzzy-TOPSIS - Faiz, Mohd Turan (2015)
The instability in today's market and the ever increasing and emerging demands for mass customized and hybrid products by customers, are driving companies and decision makers to seek for cost effective and time efficient improvement in their product development process. Design concept evaluation which is the end of conceptual design is one of the most critical decision points in product development. It relates to the final success of product development, because poor criteria assessment in design concept evaluation can rarely compensated at the later stages. This has led to real pressure for the adaption of new developmental architecture and operational parameters to remain competitive in the market. In this paper, a new integrated design concept evaluation based on fuzzy-technique for order preference by similarity to ideal solution (Fuzzy-TOPSIS) is presented. Prior to Fuzzy-TOPSIS, a new scale of "Weighting criteria" for survey process is developed to ease the rating process of evaluation criteria. Case example from industry is presented to demonstrate the efficacy of the proposed methodology. The result of the example show that the new integrated method provides an alternative to existing methods of design concept evaluation